EFEITO DE PLANTAS INSETICIDAS NO COMPORTAMENTO E BIOLOGIA DE PLUTELLA XYLOSTELLA (LEPIDOPTERA: PLUTELLIDAE) - Jesus, F.g.; Paiva, L.a. De; Gonçalves, V.c.; Marques, M.a; Boiça, A.l. [UNESP] (Instituto Biológico, 2020)
The effect of aqueous extracts of Azadirachta indica A. Juss., Sapindus saponaria L., Nim + Piretro + Rotenona, Dimorphandra mollis and Stryph nodendron adstringens (Mart) Coville was evaluated in relation to non-preference for oviposition and feeding, attractiveness and biology of Plutella xylostella. For the experiment, leaf discs from cabbage (Brassica oleracea var. acephala) plants of the Butter cultivar were immersed in each extract at the concentration 10% (weight/volume) for 30 seconds. For the no-choice test the treatments that presented less attractiveness were the extracts of A. indica and D. mollis, and the consumption was lower in A. indica. The extracts of A. indica. S. saponaria. D. mollis and S. adstringens provided a deterrent effect on oviposition of P. xylostella. The treatments A. indica. S. saponaria and S. adstringens showed a negative effect for the biological parameters of the pest.

Avaliou-se o efeito de Azadirachta indica A. Juss. (Nim), Sapindus saponaria L. (Sabão de soldado), Nim + Piretro + Rotenona, Dimorphandra mollis (Faveira) e Stryphnodendron adstringens (Mart) Coville (Barbatimão) em relação a não-preferência para oviposição e alimentação, atratividade e biologia de Plutella xylostella. Discos foliares de couve (Brassica oleracea var. acephala) cultivar Manteiga foram imersos em cada extrato à concentração de 10% (massa/volume) por 30 segundos para realização dos experimentos. Para o teste sem chance de escolha, os tratamentos que apresentaram menores atratividades foram os extratos de A. indica e D. mollis, e o menor consumo foi em A. indica. Os extratos de A. indica, S. saponaria D. mollis e S. adstringens proporcionaram efeito deterrente na oviposição de P. xylostella. Os tratamentos A. indica, S. saponaria e S. adstringens influênciaram negativamente os parâmetros biológicos da praga.
EFFECT OF INSECTICIDAL PLANTS ON THE BIOLOGY AND BEHAVIOR OF PLUTELLA XYLOSTELLA (LEPIDOPTERA: PLUTELLIDAE).
Keywords: Diamondback moth; brassica; insecticidal plant; IPM; Traça-das-crucíferas; brássicas; planta inseticida; MIP